Stability Analysis And Maximum Profit Of Logistic Population Model With Time Delay And Constant Effort Of Harvesting - Syamsuddin Toaha (Jurnal Matematika, Statistika dan Komputasi, 2006)
In this paper we develop the logistic population model by considering a time delay and constant effort of harvesting. The time delay makes the model more accurate and harvesting is incorporated since the population is beneficial or the population is under control. We study the sufficient conditions to assure the existence of the population. Perturbation method is used to linearize the model and the stability of the equilibrium point is determined by inspection of the eigenvalues. The results show that there exists a globally asymptotically stable equilibrium point for the model with and without time delay and harvesting. The time delay can induce instability and a Hopf bifurcation can occur. The stable equilibrium point for the model with harvesting is then related to profit function problem. We found that there exists a critical value of the effort that maximizes the profit and the equilibrium point also remains stable. This means that the population can exist and give maximum profit although it is harvested with constant effort of harvesting.